The Evaluation of Deterrence in University Students with Regards to Substance Use - Türk, Burcu; Yavuz, Mustafa Fatih (The Bulletin of Legal Medicine, 2018)
Objective:One of the most important components in the fight against crime is penal policies. The aim of this research is to determine the meaning of penal sanctions with regards to substance use and reveal the influence of punishment in individuals committing an offence, also whether the penalties are deterrent or not. Materials and Methods: The sample of this research is made up of students studying in universities. 277 university students participated to the gathering information phase of this research through survey method. Results:The participants stated in the following percentages that they used the below substances at least once; 17.9% marijuana, 3.4% heroine, 4.5% cocaine, 2.6% LSD, 4.5% ecstasy, 3% bonsai. 41.4% of the students think that the probability of school administration’s noticing the students using substance is low. 71.6% know substance use is a crime legally and 44.2% think that the penal sanctions given for substance use are not deterrent. 54.9 %of the students using substances and 24.1% of students not using substances think that seizure risk of a person using substances is low. When the reasons of not using substance is asked during the survey; 64% of the students stated that they believe it will be harmful for their health, while 9% declared fearing punishment and seizure depending on the risk perception of seizure. Conclusion:Per the results of the research, it is possible to state that the participants do not have clear information about the punishments imposed for substance use and about penal sanctions, their confidence to especially accuracy...